Modelos de tiempo continuo para commodities agrícolas En Colombia* (2019)
We have heard recommendations from so called “experts” suggesting the application of models to value derivatives on stocks, such as the classical Black-Scholes, to value derivatives on commodities. This practice should only be considered as a first (exploratory) step in the search for the really “fair” value. Usually, commodity prices behave quite differently from stock prices, shown here through examples from the Colombian agricultural and livestock market.